Aporte e decomposição de serapilheira em áreas de cerradão e mata mesofítica na Estação Ecológica de Pirapitinga - MG - Giacomo, Romulo Guimaraes [UNESP]; Pereira, Marcos Gervasio; Machado, Deivid Lopes [UNESP] (Universidade Federal de Santa Maria (UFSM), Centro Pesquisas Florestais, 2012)
This study aimed to quantify the litter and nutrients amount and to estimate the decomposition rate in areas of mesophytic forest and 'Cerradao' in the Ecological Station of Pirapitinga. To evaluate litter and nutrients devolution 10 conic litter traps were randomly distributed in an area 0.1 ha in each area of study, with monthly evaluations. The litter decomposition in the areas of study was evaluated by using litter bags. The total production of litter was 2.50 and 2.92 Mg ha(-1) yr(-1) for mesophytic forest and 'Cerradao' areas, respectively. The nutrients devolution importance order was nitrogen> potassium> phosphorus. The mesophytic forest showed more homogeneous distribution of litter fall over the year and higher values of total annual litter and nutrients, the highest values were observed at the dry season. The half-life decomposition of leaf litter was equivalent between areas, about 161 days in the mesophytic forest area and 173 in 'Cerradao' area.
Litter devolution and decomposition in cerradao and mata mesofitica areas in ecological station of Pirapitinga - MG
Keywords: Deciduous material; nutrient input; half time life